Change in Cerebral Perfusion after Carotid Angioplasty with Stenting Is Related to Cerebral Vasoreactivity: A Study Using Dynamic Susceptibility-Weighted Contrast-Enhanced MR Imaging and Functional MR Imaging with a Breath-Holding Paradigm - Chang, T.-Y.; Liu, H.-L.; Lee, T.-H.; Kuan, W.-C.; Chang, C.-H.; Wu, H.-C.; Wu, T.-C.; Chang, Y.-J. (American Journal of Neuroradiology, 2009)
300 Multiple ChoicesThis is a pdf-only article and there is no markup to show you.full-text.pdf